Numerical study on the effect of microgravity on biomechanics in human lumbar intervertebral discs - Bing Qin; Xin Gao; Jiwen Wu; Lu Zhou; Zhiyu Qian; Qiaoqiao Zhu (npj Microgravity)
Abstract This study was aimed to investigate the effects of microgravity on the biochemical and biomechanical change in the lumbar intervertebral disc (IVD) using a modelling approach. The lumbar IVD was considered as an inhomogeneous, porous, mixture consisting of a charged solid phase, an interstitial fluid phase, and a solute phase including charged (e.g., sodium ion, chloride ion) and uncharged (e.g., glucose, oxygen, lactate) solutes. A finite element model of the IVD was established based on the multiphase mixture theory. Our results showed that glucose and oxygen concentrations increased, while lactate concentration decreased under microgravity, compared to those under gravity condition. The metabolic rate of glucose, oxygen and lactate in the nucleus pulposus decreased, the water content increased, while the fluid pressure decreased in the IVD under microgravity compared to those under gravity. The results contribute to a better understanding of the mechanisms of microgravity related biomechanics in the human IVD.